Islamic Social Finance and the impact of the Covid-19 pandemic - N. Sh. Shirazi; L. A. Kuanova; A. S. Zhuparova (Экономика: стратегия и практика)
This paper aims to examine the spread of social tools of Islamic finance before and after the Covid-19 pandemic in Kazakhstan, as the country where Islamic finance is most promoted in the region. As a result of the absence of official and centralized information, the research has been done on an internet-based survey. The results of the research have been based on the stratified sample of 1252 respondents before and after the emergency was declared in Kazakhstan as a result of the global Covid-19 pandemic. The authors applied SPSS statistics and survey-based indicators.The findings revealed the depth of awareness of social tools of Islamic finance, understanding of the main principles of Zakat and Sadaqah and difference of them. It was found that the age of the respondents has positive effects on the periodicity and amount of the donations. Furthermore, the results showed that the absence of a centralized system of charity in the country and the mistrust of intermediaries inhibit the development of Islamic finance instruments and lead to donations directly to needy people. The major constraints impeding Islamic social finance include the underdevelopment of Islamic finance as a value-based financial system.Islamic social finance tools could be both a resource and a solution for solving sustainability issues during and after the pandemic period in the country. The authors identified the impact of the Covid-19 pandemic on the structure of the charity projects, on the increase of the demand for financial assistance by individuals and the income decrease of the donators.